High arctic vegetation after 70 years: a repeated analysis from Svalbard - Prach, K. (Karel); Košnar, J.; Klimešová, J. (Jitka); Hais, M. (Polar Biology, 2010)
The mapping did not reveal changes in vegetation over the past 70 years that could be attributed to climate change; but some successional changes were due to erosion-accumulation processes connected especially to stream activity. This may be probably explained by either (i) a lack of significant change in climate when comparing the 1930s and the 2000s or (ii) the slow ecological response of constituent plants in such a harsh environment. We argued in favour of the latter explanation. Moreover, geographic isolation may limit establishment and expansion of new species.